2017
DOI: 10.1111/jph.12667
|View full text |Cite
|
Sign up to set email alerts
|

A COI1 gene in wheat contributes to the early defence response against wheat powdery mildew

Abstract: The hormone jasmonate (JA) signalling pathway is involved in diverse developmental processes in plants. COI1 is a key regulator in JA pathway. Although COI1 homologous proteins have been identified in a variety of crops, their regulatory mechanisms in wheat defence responses remain unknown. Here, we cloned COI1 from disease resistant wheat Brock, designated TaCOI1. TaCOI1 cDNA was 1988‐bp long, with an ORF encoding 593 deduced amino acids. The phylogenetic tree showed that TaCOI1 was clustered in the same clad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 30 publications
0
13
0
Order By: Relevance
“…We could not detect the expression of TaOPR2 homeolog genes from the A and D genomes, either because of the low expression level of these genes in leaf tissue, or because of the sequence difference between Saratovskaya-60 and the sequenced wheat varieties. The expression level of the jasmonate receptor COI-1 ( TaCOI-1 ) [31] was not altered in transgenic lines (Figure 2C). The gene expression analysis demonstrates that AtOPR3 gene overexpression selectively affects some genes of the endogenous jasmonate system, while the expression of other genes remains unaltered.…”
Section: Discussionmentioning
confidence: 99%
“…We could not detect the expression of TaOPR2 homeolog genes from the A and D genomes, either because of the low expression level of these genes in leaf tissue, or because of the sequence difference between Saratovskaya-60 and the sequenced wheat varieties. The expression level of the jasmonate receptor COI-1 ( TaCOI-1 ) [31] was not altered in transgenic lines (Figure 2C). The gene expression analysis demonstrates that AtOPR3 gene overexpression selectively affects some genes of the endogenous jasmonate system, while the expression of other genes remains unaltered.…”
Section: Discussionmentioning
confidence: 99%
“…In a previous study, we analysed early resistance responses of the resistant wheat variety ‘Brock’, a susceptible variety ‘Jing411’ and their NIL ‘BJ‐1’ to powdery mildew infection. Early response gene of wheat to powdery mildew ( TaCOI1 ) was cloned and analysed, and it was observed that expression of TaCOI1 in resistant ‘Brock’ was earlier than that in susceptible line (Li et al., 2014; Liu et al., 2018). Transcriptome analysis showed that ‘Brock’ began to react to powdery mildew after 2 hpi, and multiple disease‐related genes were detected after 12 hpi (unpublished).…”
Section: Discussionmentioning
confidence: 99%
“…Average time of ETI in ‘Brock’ occurred at 12 hpi (L. Zhang, X. Liu, Z. Wang, Unpublished data). These results demonstrated that the interaction between powdery mildew and wheat occurred in the early stages of inoculation and that the response rate of wheat to powdery mildew was directly related to disease resistance at the seedling stage (Li et al., 2014; Liu et al., 2018).…”
Section: Introductionmentioning
confidence: 90%
See 2 more Smart Citations